Territorial government and flexibility: a critical assessment - Petr Dostál (Belgeo)
The paper examines the character of multipurpose territorial government and explores the meaning of frequent calls for more flexibility in the structures and functioning of local and regional governments. The paper elaborates on a number of starting points of debate concerned with the shift from territorial government to territorial governance. Configurations of territorial governance are operating within a broader and more diverse range of factors at both local and regional levels. These include non-elected agencies of the state, private businesses, voluntary organisations, the mass media, and EU institutions. Situations of diffused accountability arise from continuing interactions between network partners, exchange of resources and negotiation of shared purposes, and they constrain the field of democratic accountability. Importantly, one of the key characteristics of the shift from government to governance is claimed to be increased flexibility and responsiveness, in both the functioning and the structure of territorial government. Finally, building on the foregoing, the paper emphasises the issue of public interest formation and aggregation, and the adverse impacts of the fragmentation on the integrative territorial competence of multipurpose governments. The critical assessment provided shows that the notion of flexibility appears to refer to the capability to react to unpredictable future developments by enlargement of management capacity through new steering and decision-making rules. Correspondingly, flexibility does not necessarily refer to changing the existing organisational structures of territorial self-government and administration but primarily to adaptations of their mode of functioning and, therefore, to increasing flexibility of rules and approaches.